Adenoid Cystic Carcinoma of the Trachea - Nabi, Nosheen; Khalid, Ahmareen; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Adenoid cystic carcinoma is a malignant tumor of salivary glands. It is extremely rare in trachea worldwide. They arise in the subepithelioal minor salivary glands, grow slowly and metastasize by perineural invasion. Patient usually presents with dyspnea. It is diagnosed by histopathological evaluation of biopsy taken by endoscopy. Its treatment includes surgical resection with or without radiotherapy. They frequently recur after initial treatment.